2017
DOI: 10.3390/ijms18040816
|View full text |Cite
|
Sign up to set email alerts
|

CoQ10 Deficiency May Indicate Mitochondrial Dysfunction in Cr(VI) Toxicity

Abstract: To investigate the toxic mechanism of hexavalent chromium Cr(VI) and search for an antidote for Cr(VI)-induced cytotoxicity, a study of mitochondrial dysfunction induced by Cr(VI) and cell survival by recovering mitochondrial function was performed. In the present study, we found that the gene expression of electron transfer flavoprotein dehydrogenase (ETFDH) was strongly downregulated by Cr(VI) exposure. The levels of coenzyme 10 (CoQ10) and mitochondrial biogenesis presented by mitochondrial mass and mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Apoptosis, which is characterized with nuclear fixation, cell shrinkage, DNA fragmentation, and cell membrane bubbles, is a tightly controlled cell death pattern [ 20 , 21 ]. The extrinsic pathway, named the death-receptor pathway, and the intrinsic pathway, named mitochondria-dependent pathway, are the two crucial pathways that are related to apoptosis [ 22 ]. The intrinsic pathway is mediated by Bcl-2 protease family which include apoptotic factors (Bax, Bim, Bak, Noxa, et al) and anti-apoptotic factors (Bcl-2, Mel-1, Bcl-w, et al).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis, which is characterized with nuclear fixation, cell shrinkage, DNA fragmentation, and cell membrane bubbles, is a tightly controlled cell death pattern [ 20 , 21 ]. The extrinsic pathway, named the death-receptor pathway, and the intrinsic pathway, named mitochondria-dependent pathway, are the two crucial pathways that are related to apoptosis [ 22 ]. The intrinsic pathway is mediated by Bcl-2 protease family which include apoptotic factors (Bax, Bim, Bak, Noxa, et al) and anti-apoptotic factors (Bcl-2, Mel-1, Bcl-w, et al).…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are engendered in the oxidation-reduction procedure [ 1 ]. ROS, as products of the oxidation and peroxidation process, are instantaneously detoxified by ROS scavengers and antioxidants under physiological conditions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquinone (UB), also known as coenzyme Q10 [ 15 , 16 ], is a coenzyme that is regarded as a vitamin-like lipid soluble substance [ 17 , 18 , 19 ]. UB is a vital cofactor in the mitochondrial respiratory chain and plays a fundamental role in oxidative phosphorylation to allow ATP production [ 1 , 20 , 21 ]. Accordingly, UB plays a critical role in energy biosynthesis within the cells and serves as a cofactor in cellular bioenergetics [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the toxic mechanism of hexavalent chromium Cr(VI) and to search for an antidote for Cr(VI)-induced cytotoxicity, a study of mitochondrial dysfunction induced by Cr(VI) and cell survival by recovering mitochondrial function was performed by Zhong et al [ 12 ]. They found that the gene expression of electron transfer flavoprotein dehydrogenase (ETFDH) was strongly downregulated by Cr(VI) exposure.…”
mentioning
confidence: 99%